Job Search during the COVID-19 Crisis - Lena Hensvik; Thomas Le Barbanchon; Roland Rathelot (Institute of Labor Economics (IZA), 2020)
This paper measures the job-search responses to the COVID-19 pandemic using realtime data on vacancy postings and ad views on Sweden's largest online job board. First, the labour demand shock in Sweden is as large as in the US, and affects industries and occupations heterogeneously. Second, the scope and direction of search change. Job seekers respond to the shock by searching less intensively and by redirecting their search towards less severely hit occupations, beyond what changes in labour demand would predict. The redirection of job search changes relative hiring costs, and has the potential to amplify labour demand shifts.
Keywords: J22; J23; J21; J62; J63; J64; E24; 330; COVID-19; coronavirus; search intensity; search direction; labour demand shock; job vacancies; online job board